Analisis Yuridis Tindak Pidana Judi Offline dan Tindak Pidana Judi Online di Kota Kupang - Adi Putra Bolle; Bhisa V. Wilhelmus; Daud Dima Tallo (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
In East Nusa Tenggara (NTT) there are various types of gambling, ranging from offline gambling to online gambling. In the city of Kupang itself there are various kinds of gambling, starting from offline gambling, namely, kuru-kuru or throwing dice, rolling ball, cockfighting or cockfighting and bingo, as well as online gambling which is usually called lottery gambling or white coupons. In short, gambling itself is the action of a person or a number of people in risking a certain amount of money or objects in order to seek profit and includes all kinds of bets in the form of money or objects, either directly or indirectly, such as online payments via online applications or existing online sites to facilitate transaction. This research uses normative legal research methods sourced from data obtained in the form of legal rules, legal principles and legal doctrines to answer the problems studied. The research results show that the occurrence of gambling in Indonesia to date is one of the factors caused by the weaknesses in the regulations regarding criminal acts of gambling offline and online so that gambling in Indonesia is still very widespread.